Pendampingan Penyusunan Hand Out Olimpiade Matematika di SDN Madyopuro IV Malang - Rosyadi, Alfiani Athma Putri; Khusna, Arif Hidayatul (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Mathematics Olympiad is one of the routine activities followed by school level, especially elementary school. One of the elementary schools that regularly participates in the Olympic competition is SDN Madyopuro 4 Malang. Based on the results of interviews with teachers, information was obtained that at SDN Madyopuro 4, the Olympic guidance activities were still not optimal. In addition, there is also no Hand Out provided specifically for Olympic activities. This is what makes the service team to provide training and assistance to teachers at the elementary school. The implementation method of this activity consists of five stages of activities, namely preparation, socialization, mentoring, implementation and evaluation. The result of this service activity was that preparations were carried out with the Olympic team running smoothly, then the socialization was carried out by a team together with elementary school teachers which was originally scheduled to be face-to-face but was replaced online due to the covid-19 pandemic. Overall, the assistance activities for the preparation of hand outs went well and smoothly. The use of Hand Out for students during face-to-face meetings both offline and online also helps the implementation of Olympic mentoring activities. Suggestions for the next activity is to collaborate with appropriate learning strategies, models and approaches so that they can produce maximum results.